Island of the Blue Dolphins - O'Dell, Scott, 1898-1989. (New York : Yearling Book, 2005)
Left alone on a beautiful but isolated island off the coast of Calif ornia, a young Indian girl spends eighteen years, not only merely survi ving through her enormous courage and self-reliance, but also finding a measure of happiness in her solitary life.